Pattern of Presentation and Management of Ectopic Pregnancy in Tertiary Care Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Ectopic pregnancy is a life threatening complication of the first trimester of pregnancy that arises in 1.3 – 2.4% of all pregnancies.Objective: The aim of this study was to determine the frequency of ectopic pregnancy and to evaluate the clinical presentation, risk factors and management outcomes of ectopic pregnancies.Methods: This was a retrospective, descriptive study of ectopic pregnancies managed at Dhaka Community Medical College Hospital during the period of January 2013 to December 2017. Total 70 cases of ectopic pregnancies were included. The medical records of the patients managed for ectopic pregnancies were retrived and data were collected from registers. The relevant data were analyzed with simple descriptive statistics and presented in frequency chart and tables.Results: Total 70 cases of ectopic pregnancies were managed during the study periods which constituted 3.6% of all gynaecological admissions. Most of the patients (35.7%) were between 25 – 29 years age group. It was most common in multiparae with a percentage of 85.7% . The commonest (92.9% ) clinical presentation was abdominal pain. Almost 14.3% were in a state of shock at admission. Among the identified risk factors 28.6% had a previous history of induced abortion and 22.9% had pelvic inflammatory disease. Out of 70, 60 patients (85.7%) had ruptured ectopic pregnancies, 4 (5.7%) were unruptured and 5 (7.1%) produces a complex tubo-ovarian mass. Only 1(1.4%) case was presented early & treated with intramuscular methotrexate injection. Surgery by open method in the form of salpingectomy 64(91.4%) and salpingo-oophorectomy 5(7.1%) were the mainstay of management. No maternal mortality found in this series.Conclusions: Since ectopic pregnancy remains a gynaecological catastrophe in developing countries and a major challenge to the reproductive performance of women worldwide, it should be considered a relevant public health issue. Early diagnosis, identifying of underlying risk factors and timely intervention in the form of conservative or surgical treatment will help in reducing the morbidity and mortality associated with ectopic pregnancy.Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 28-32